ARCHITECTURAL STUDY OF SHRINE OF HAZRAT SULTAN BAHU - Humera Omer Farooq; Rabea Saeed-Hassan; Dr. Aqsa Malik; Farrukh Hammad Rasool; Rabail Qureshi (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2023)
The approach taken herein to the study of Sultan Bahu’s shrine is a multi-dimensional one. The history of, purpose for, and the function of Bahu’s shrine along with how it is a gateway to understanding Sufi mysticism is what will be discussed. As well as that, we will investigate his philosophy and how it drove his poetry and influenced his mysticism.